Internalisasi Nilai - Nilai Tasawuf Dalam Pembentukan Sikap Moderasi Beragama - Mujahidin Mujahidin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
There are three aims of this research, namely to describe the values of Sufism, explain the process of internalizing Sufism and describe the relevance of internalizing Sufism values in forming an attitude of religious moderation in the Thoriqoh Syadziliyah Al Masudiyah Jombang Congregation. The Sufism values taught include Simplicity (Zuhud), Humility (Tawadhu'), Compassion and Kindness (Ihsan), Patience and Perseverance (Sabr), Rejection of Negative Lust (Mujahadah). The process of internalizing Sufism is influenced by supporting factors and challenges in implementation. Supporting factors: Thoriqoh Syadziliyah, which is muktabaroh and famous for its easy practices for the congregation. Challenging/inhibiting factors: Struggle with Ego and Worldly Desires, Maintaining Spiritual Discipline, Negative Environmental Influences. The relevance of internalizing Sufism values in forming attitudes of religious moderation. By practicing the values of Sufism, the thoriqoh congregation will form a high attitude of tolerance. By practicing Sufism, the congregation has openness and inclusiveness (tawas), which encourages religious moderation. With a simple lifestyle and Zuhud, the congregation is not easily provoked into committing terrorism and other intolerance. A balanced lifestyle meets the needs of the world, and Akirat helps to encourage the stability of religious harmony in the surrounding environment